Thinking about teaching and learning : developing habits of learning with first year college and university students - Leamnson, Robert. (Trentham, 1999)
Thinking about thinking about teaching. The biological basis of learning. Language. Today's first-year students. Teaching and pedagogy. The classroom. Writing and other technologies. Final thoughts.